2021
DOI: 10.2147/dmso.s342647
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from β-Cells Promote Differentiation of Induced Pluripotent Stem Cells into Insulin-Producing Cells Through microRNA-Dependent Mechanisms

Abstract: Objective Exosomes have emerged as potential tools for the differentiation of induced pluripotent stem cells (iPSCs) into insulin-producing cells (IPCs). Exosomal microRNAs are receiving increasing attention in this process. Here, we aimed at investigating the role of exosomes derived from a murine pancreatic β-cell line and identifying signature exosomal miRNAs on iPSCs differentiation. Methods Exosomes were isolated from MIN6 cells and identified with TEM, NTA and Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Emerging data suggest that miRNAs play a pivotal role in IPCs differentiation from diverse stem cells [10]. Guo et al indicated that the differentiation of induced pluripotent stem cells into IPCs is dependent on miRNA-related mechanisms [26]. MiRNA-101a and miRNA-107 showed prominent expression during the differentiation of adipose-derived mesenchymal stem cells into IPCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data suggest that miRNAs play a pivotal role in IPCs differentiation from diverse stem cells [10]. Guo et al indicated that the differentiation of induced pluripotent stem cells into IPCs is dependent on miRNA-related mechanisms [26]. MiRNA-101a and miRNA-107 showed prominent expression during the differentiation of adipose-derived mesenchymal stem cells into IPCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of these exosomes into STZ-induced diabetic mice improved glucose tolerance, increased the insulin content, and preserved the architecture of pancreatic islets. Guo and associates cocultured exosomes derived from a mouse insulinoma cell line (MIN6) with human iPSCs for 21 days [ 95 ]. After 7 days of coculture, the proportion of insulin-positive cells by flow cytometry was 22.3% in the exosome-treated cell population, while it was only 11.9% among the controls.…”
Section: Msc-derived Exosomes and Diabetes Mellitusmentioning
confidence: 99%
“…EVs and exosomes in particular, have been found to play a crucial role in different biological processes, including: cell signaling, neuronal function [46], tissue regeneration [47], intercellular communication [48], immune function [49], development and differentiation of stem cells [50], cancer life cycle [51,52] and viral replication [53]. EVs have the ability to transfer their cargo and to be selectively taken up by specific cells, thereby reprogramming the target cell and, possibly, inducing or preventing disease.…”
Section: Milk-derived Extracellular Vesicles In Health and Diseasementioning
confidence: 99%